MENINGKATKAN HASIL PEMBELAJARAN SEPAK BOLA MENGGUNAKAN PERMAINAN SEPAK BOLA MINI PADA SISWA KELAS V SDN 6 SELATPANJANG SEMESTER 1 TAHUN PELAJARAN 2019 / 2020 - Mardiana Mardiana (Jurnal Guru Kita PGSD, 2020)
Abstract: Improving the Learning Outcomes of Football Using Mini Football Games for Class V SDN 6 Selatpanjang Students Semester 1 Academic Year 2019/2020. This study aims to improve the results of learning football using mini football games in Class V SDN 6 Selatpanjang students Semester 1 in 2019. This research uses the Classroom Action Research (CAR) method. The procedure of this research includes planning, acting, observing and reflecting which are carried out in 2 cycles with two meetings in each cycle. The subject of this research is the fifth grade students of SDN 6 Selatpanjang in Semester 1 of the 2019/2020 Academic Year. The research subjects were 20 students. Data collection techniques were through tests and observations of cognitive, affective, psychomotor aspects and student activities. Data validation used 2 types of triangulation, namely triangulation of sources and triangulation of techniques. The data analysis technique used in this study was descriptive. . The results of the data analysis showed that the cognitive aspects of the initial condition were 7 students completed or 35.00%, in cycle I the percentage of student completeness reached 55.00% or 11 students and in cycle II the percentage of student completeness reached 95% or 19 students, with the acquisition of an average value of learning outcomes from 59.50 to 67.50 and 77.00 in the second cycle. The affective aspect in the initial conditions was 50% or 10 students, in the first cycle the average percentage of attitude observations reached 80% or 16 students and in cycle II, the average percentage of attitude observation reached 100% or 20 students. Psychomotor aspects in the initial condition of 4 students or 20% of students were declared complete, in cycle I, the percentage of completeness of students' psychomotor skills reached 75% or 15 students and in cycle II, the average percentage of psychomotor skills reached 95%. Observation of student activity in the initial condition was 50.00% or 10 students, in cycle I the average percentage of student behavior observations was 80% or 16 students and in cycle II the average percentage of student behavior was 95% or 19 students. Thus the action of learning football by implementing mini football games for fifth grade students of SDN 6 Selatpanjang is successful. And it is hoped that Physical Education teachers in elementary schools can apply mini-football games to students in learning Physical Education, Sports and Health. Keywords: Mini Football, Learning Outcomes Abstrak: Meningkatkan Hasil Pembelajaran Sepak Bola Menggunakan Permainan Sepak Bola Mini Pada Siswa Kelas V Sdn 6 Selatpanjang Semester 1 Tahun Pelajaran 2019 / 2020. Penelitian ini bertujuan untuk meningkatkan hasil pembelajaran sepakbola menggunakan permainan sepakbola mini pada siswa Kelas V SDN 6 Selatpanjang Semester 1 Tahun 2019/2020.Penelitian ini menggunakan metode Penelitian Tindakan Kelas (PTK).Prosedur penelitian ini meliputi planning, acting, observasi dan reflecting yang dilaksanakan dalam 2 siklus dengan dua pertemuan pada masing-masing siklusnya.Subjek  penelitian  ini  adalah  siswa  kelas  V  SDN 6 Selatpanjang   pada Semester 1 Tahun Pelajaran  2019/2020. Subjek penelitian sebanyak 20 siswa.Teknik pengumpulan data adalah melalui tes dan observasi aspek kognitif, afektif, psikomotorik dan aktivitas siswa.Validasi data menggunakan 2 jenis triangulasi, yaitu triangulasi sumber, dan triangulasi teknik.Teknik analisis data yang digunakan dalam penelitian ini adalah secara deskriptif. Hasil analisis data hasil penelitian menunjukkan bahwa aspek kognitif dari kondisi awal terdapat 7 siswa tuntas atau 35,00%, pada siklus I persentase ketuntasan siswa mencapai 55,00%  atau 11 siswa dan pada siklus II persentase ketuntasan siswa mencapai 95% atau 19 siswa, dengan perolehan nilai rata-rata hasil belajar dari 59,50 menjadi 67,50 dan 77,00  pada siklus kedua.Aspek afektifpada kondisi awal sebesar 50% atau 10  siswa, pada siklus I persentase rata-rata pengamatan sikap mencapai 80% atau 16 siswa  dan pada siklus II, persentase rata-rata pengamatan sikap mencapai 100% atau 20  siswa. Aspek psikomotorik pada kondisi awal 4 siswa atau 20% siswa dinyatakan tuntas, pada siklus I, persentase ketuntasan  keterampilan psikomotor siswa mencapai 75%  atau  15 siswa serta pada siklus II, persentase rata-rata keterampilan psikomotor mencapai 95%. Pengamatan aktivitas siswa pada kondisi awal sebesar 50,00% atau 10 siswa, pada siklus I persentase rata-rata pengamatan perilaku siswa sebesar  80%  atau 16 siswa dan pada siklus II persentase rata-rata perilaku siswa sebesar 95% atau 19  siswa.   Dengan demikian tindakan pembelajaran sepakbola dengan menerapkan permainan sepakbola mini pada siswa Kelas V SD Negeri SDN 6 Selatpanjang dapat dikatakan berhasil.Dan diharapkan bagi guru Pendidikan Jasmani di Sekolah Dasar untuk dapat menerapkan permainan sepakbola mini pada siswa dalam pembelajaran Pendidikan Jasmani, Olahraga dan Kesehatan. Kata Kunci :Sepak Bola Mini, Hasil Pembelajaran